Fabrication of ZnO-NiO nanocomposite thin films and experimental study of the effect of the NiO, ZnO concentration on its physical properties. (15th November 2017) - Thamri, S.; Sta, I.; Jlassi, M.; Hajji, M.; Ezzaouia, H.
Abstract: ZnO-NiO nanocomposites thin films were elaborated at different mixing concentrations using sol gel and spin coating methods. Their structural and morphological evolutions as well as the optical and electrical properties were investigated. XRD diffraction and Raman spectra allowed phase identifications of ZnO (zinc oxide) and NiO (nickel oxide) with no appearance of secondary phases and the crystallinity of elaborated nanocomposite films improved with doping concentration increase. The grain sizes of obtained ZnO-NiO nanocomposites are investigated by AFM (Atomic force microscopy); they increase in the range (10–65 nm) and they are observed to affect the optical and electrical properties. In fact, ZnO-NiO nanocomposites thin films optical reflectivity decreased in the range (10–5%) with the increasing of mixing proportion and their resistivity decreased up to 1.4 10 2 Ω cm. The optical band gaps were in the range (3.3–4 eV). The values obtained by UV–Vis spectroscopy and ellipsometry are quite similar. We remarked also that the NiO concentration increase on to the nanocomposite induced a red shift of the gap value while the ZnO increase led toward a blue shift